Penerapan Integrated Marketing Communication (IMC) pada UMKM Dobakes - Golan Hasan; Ella Kristia; Sahda Fatonah Salsabila Sopyan; Celyne Chintya Yan; Sharfina Intan Nuraini (LPPM STIE KRAKATAU, 2025)
Abstract This article discusses the implementation of Integrated Marketing Communication (IMC) in UMKM DoBakes as part of a social media content management project. The purpose of this study is to improve brand visibility, social media engagement, and operational effectiveness through structured content planning and digital communication strategies. The findings show significant improvements in content reach, interactions, follower growth, and customer awareness after the application of IMC-based content scheduling. These results highlight the importance of consistent communication and integrated promotional tools in building strong brand awareness for small businesses operating in competitive digital environments. Keywords: IMC, digital marketing, social media management, brand awareness Abstrak Artikel ini membahas penerapan Integrated Marketing Communication (IMC) pada UMKM DoBakes sebagai bagian dari program pengelolaan konten media sosial. Tujuan kegiatan ini adalah meningkatkan visibilitas merek, keterlibatan pengguna, serta efektivitas operasional melalui penyusunan jadwal konten dan strategi komunikasi digital yang lebih terarah. Hasil analisis menunjukkan adanya peningkatan signifikan pada jangkauan konten, interaksi, pertumbuhan pengikut, dan kesadaran pelanggan setelah penerapan jadwal konten berbasis IMC. Temuan ini menegaskan bahwa konsistensi pesan dan integrasi saluran komunikasi memiliki peran penting dalam membangun brand awareness pada UMKM yang bersaing di era digital. Kata Kunci: IMC, komunikasi pemasaran, media sosial, UMKM